Long term follow-up of a randomised controlled trial of services for urinary symptoms - Cooper Nicola J; Assassa R Philip; Shaw Christine; Turner David A; Abrams Keith R; Coleby Dawn; Williams Kate S; Donaldson Madeleine MK; McGrother Catherine W (BMC, 2011)
Abstract Background Given the extent and priority of urinary symptoms there is little evidence available to inform service provision in relation to the long term effects of interventions. This study aims to determine the long term (6 year) clinical effectiveness and costs of a new continence nurse led service compared to standard care for urinary symptoms. Methods A long term follow-up study of a 2-arm, non-blinded randomised controlled trial that recruited from a community based population between 1998-2000 in Leicestershire and Rutland UK was undertaken. 3746 men and women aged 40 years and over were followed up from the original trial. The continence nurse practitioner (CNP) intervention comprised a continence service provided by specially trained nurses delivering evidence-based interventions using pre-determined care pathways. The standard care (SC) arm comprised access to existing primary care including General Practitioner and continence advisory services in the area. Primary outcome: Improvement in one or more symptom. Secondary outcomes included: a) Leicester Impact scale; b) patient perception of problem; c) number of symptoms alleviated and cost-effectiveness; all were recorded at long term follow-up (average 6 years) post-randomisation. Results Overall at long-term follow-up (average 6 years) significantly more individuals in the CNP group (72%) had improved (i.e had fewer symptoms) compared to those in the SC group (67%) (difference of 5% 95% (CI = 0.6 to 9;p = 0.02)). Conclusion The differences in outcome between the two randomised groups shown immediately post treatment had decreased by half in terms of symptom improvement at long term follow-up. Although the difference was statistically significant, the clinical significance may not be, although the direction of the difference favoured the new CNP service.